Impacts of the Representative Market Rate Using Statistical Models, Sectoral Study - Merchan Jiménez, Leidy Bibiana; Restrepo Quiroz, Jorge Andrés; Valencia Cárdenas, Marisol; Caridad Faria, Migdalia Josefina (Sociedad y Economía, 2023)
This paper analyzes the impact of the exchange rate fluctuations on the financial performance of the pork sector in Colombia. The exchange rate, measured by the Representative Market Rate (RMR), affects the costs and profitability of the swine business, which is influenced by the international market. The paper uses a quantitative research methodology with a correlational approach, applying Pearson correlation tests and statistical models to estimate the effects of the RMR on the costs and profit margin of the sector, as well as to forecast the future behavior of the RMR. The paper finds that the RMR has a high volatility and a significant correlation with most of the costs, which negatively affects the profit margin, especially when the RMR increases. The paper also proposes a forecasting model for the RMR based on its own past values and an autoregressive integrated moving average (ARIMA) model for the residuals.